A cidade, suas tramas e seus dramas: urbanização e imigração em Imperatriz/MA (1950 a 1980) - Carvalho, Sheryda Lila de Souza (Universidade do Vale do Rio dos Sinos, 2022)
The historiography produced about the city of Imperatriz/MA is marked by a developmental discourse based on the “vocation of the city for progress”, under the command of a small economically and politically dominant group. Despite this, what is actually observed is a trajectory signed by great contrasts. Thus, historically, a city is perceived as symbolised by both the progressive discourse and the maintenance of a status quo of needs and problems. We are specifically interested in the issues related to its urbanisation, which today reflect the consequences of the strong population growth experienced in the mid-twentieth century, especially in the period after the Belém-Brasília highway opening. In this context, the present study aims to understand, from historical sources, the contradictions and singularities that permeate the history of urbanisation in Imperatriz, strongly marked by the presence of migratory flows. From the content analysis applied to the newspaper O Progresso and the oral history of people who came from the Northeast to settle in this city, we seek to understand how the insertion of northeastern immigrants in the urban space of Imperatriz took place, in terms of adaptation and city use. Faced with the population increase resulting from immigration, the urbanisation process is established and the city's position in the regional scenario is transformed, making it a regional reference centre. Understanding the experiences of Imperatriz in the presented perspective contributes to a social history of urban space that is unprecedented in the scientific production on this city, which lacks studies on migration and its effects on local urbanisation.
Keywords: Urbanização; Imigração; Cidade; Progresso; Imperatriz; Urbanisation; Immigration; City; Progress; ACCNPQ::Ciências Humanas::História